Musicology - Kerman, Joseph (Collins Fontana Press, 1985)
Crammed into this 230-page paperback is an extremely erudite account of American and British musicology and its growth in the second half of the 20th century. Kerman carefully distinguishes musicology - the history of Western art music - from music theory (and analysis), ethnomusicology, and music criticism.Music can obviously be studied internally, that is, its form or structure can be analysed in respect of harmony, melody, rhythm and so on. The music "stands on its own" without words or pictures or other iconic reference beyond itself. What then is the relationship between this kind of investigation and the work of placing music in a social, historical, cultural or economic context? What sort of theories have been developed to handle an already abstract subject-matter? How does this theorizing relate to work in other fields, such as literary theory and aesthetics? Given the avowedly mathematical nature of much contemporary composition, how can it be understood without recourse to yet more abstract theory?Who is in a position to assess the theorizing? Kerman mentions the first issue of the journal, Perspectives, which contained a review of another journal, Die Reihe, by a professor of physics, who "demonstrated that the scientific terminology that is so prominent in all the articles - including those by the editors, Eimert and Stockhausen - was used without the least understanding of its actual scientific meaning".Ethnomusicology has been defined as the study of music in culture, and Kerman outlines alternative understandings of this discipline, including the idea that it should be construed as a branch of cultural anthropology rather than as the province of the historian. But should musicology accept that it is a sub-set of ethnomusicology? This too is in dispute."In the famous 'Overture' to 'The Raw and the Cooked', ... Lévi-Strauss singled out music and myth as the two most promising areas for the structural analysis of culture. Having so pronounced, Lévi-Strauss wrote his wrong-headed account of Ravel's Bolero. Otherwise he has all but completely ignored music - actual music, as opposed to ideas about it - and one can sympathize with the frustration of ethnomusicologists as they struggle to make themselves heard in the seemingly tone-deaf conclaves and enclaves of anthropology."